Compact and wide-band bismuth-based erbium-doped fibre amplifier based on two-stage and double-pass approaches - Cheng, X.S.; Hamida, Belal Ahmed; Ahmed Wathik, Naji; Hamzah, Arof; Harith B., Ahmad; Harun, Sulaiman Wadi (Inst Engineering Technology-Iet, 2012)
In this study, a wide-band erbium-doped fibre amplifier (EDFA) operating in both C- and L-band wavelength regions is demonstrated based on two-stage and double-pass approaches. The amplifier employs two pieces of 21 and 46 cm long bismuth-based EDFs (Bi-EDFs) optimised for C- and L-band operations, respectively, which are pumped by 1480 nm laser diode and its performances are investigated in both parallel and linear configurations. Wide-band operation is achieved in both configurations that covers from 1525 to 1620 nm. Compared with the linear Bi-EDFA, the parallel Bi-EDFA provides a higher attainable gain especially for small input signal. At input signal power of -30 dBm, the average gains of the parallel Bi-EDFA are obtained at approximately 20 dB with gain variation of ±2.5 dB within the wavelength region from 1530 to 1605 nm. At the input signal power of 0 dBm, the average gains of approximately 10 dB with a gain variation of ±2 dB within 1540 to 1620 nm region are obtained by both parallel and linear Bi-EDFAs. The noise figures for both configurations are maintained below 10 dB in the wavelength region from 1535 to 1620 nm. The noise figures are mainly because of spurious reflection in the cavity and high reflection of amplified spontaneous emission (ASE) from the end face.